Long Covid requires a global response centred on equity and dialogue - Larry Au; Cristian Capotescu; Amanda Curi; Renan Gonçalves Leonel da Silva; Gil Eyal (Taylor & Francis Group, 2023)
Long Covid, or Post-Covid Conditions, is a global health problem. Yet we know strikingly little about the different experiences of Long Covid patients cross-nationally. To address this shortcoming, we conducted an online survey of Long Covid patients active on social media in the U.S. (n = 334, October to December 2021) and Brazil (n = 144, January to April 2022). Our analysis of short answer responses indicates patient dissatisfaction with medical care provided for Long Covid in both the U.S. and Brazil. For Long Covid patients in Brazil, there were additional concerns raised about the lack of local expertise about their condition. Based on these results, we urge policymakers to expand the education of medical professionals in order to raise awareness of Long Covid. Experts in the Global North should also be encouraged to engage in dialogue with patient groups and experts in the Global South, in order to better understand how local contexts shape the experience of Long Covid.